Morals of Faith Teaching at Madrasah Aliyah Daru al Da'wah wa al Irsyad (DDI) Salumbia Dondo District Tolitoli Regency - Kamaruddin Kamaruddin; Ulil Amri; Askar Askar (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2022)
Implementation of morals of faith Learning is the central pillar in shaping the character of good students so that schools have their value in implementing educational programs. This study aims to determine the entire series of implementation of morals of faith learning in madrasas. The study used qualitative methods with data collection techniques through observation, in-depth interviews and written documents. Based on the results of data analysis using Behavioristic learning theory, it shows that the learning of morals of faith is carried out by reinforcing the form of advice before and after the learning is carried out. Then students are given a stimulus in the form of awards when learning is carried out well and given guidance again if students have not achieved the learning objectives well. Furthermore, the teacher adapts according to the learning conditions faced in the classroom. This study also shows that learning morals of faith is to instil a strong belief in students in Allah SWT. This form of learning is carried out through direct face-to-face and online learning (E-Learning). Morals of faith learning is also carried out in a combination between lectures, question and answer discussions and exemplary methods.